ANALISIS PERMEABILITAS TANAH LAPISAN ATAS DAN BAWAH DI LAHAN KOPI ROBUSTA - Febri Ayu Alista; S Soemarno (Departemen Tanah, Fakultas Pertanian, Universitas Brawijaya, 2021)
Coffee (Coffea sp.) is one of the leading commodities in Indonesia for it has a high economic value. In Bangelan Village, Malang Regency, there is a company that manages robusta coffee commodity. The land was converted into a coffee plantation from forest land. The conversion of forest land into a coffee plantation caused the decreasing number of total soil pores lower than the forest land. This will make it difficult for water to absorb into the soil. This research was conducted in Afdeling Besaran, PT. Perkebunan Nusantara XII Kebun Bangelan to elucidate the value of soil permeability and the nature of the relationship between them. The result of this research indicated that the permeability of the soil on each land map unit was in the category of fast permeability class and slightly fast permeability class. The highest soil permeability value was found on land map unit 2 at the 56 years average age of coffee robusta field, with each depth of 6.03 cm hour-1, 7.95 cm hour-1, and 7.82 cm hour-1. Soil permeability is influenced by soil porosity, sand and silt with a positive correlation way. In addition, aggregate stability, soil bulk density and clay also significantly affected the soil permeability with a negative correlation way. Permeability affected the production of robusta coffee plants with a positive correlation way of 16.09%.